The Diatom/Dinoflagellate Index as an Indicator of Ecosystem Changes in the Baltic Sea 1. Principle and Handling Instruction - Wasmund, Norbert; Kownacka, Janina; Göbel, Jeanette; Jaanus, Andres; Johansen, Marie; Jurgensone, Iveta; Lehtinen, Sirpa; Powilleit, Martin (Frontiers in Marine Science, 2017)
An ecosystem shift in the Baltic Proper at the end of the 1980s could be identified by a decreasing springtime diatom/dinoflagellate ratio. Therefore the suggested diatom/dinoflagellate index (Dia/Dino index) was developed as a descriptive indicator of ecosystem changes for applications pertaining to the Marine Strategy Framework Directive (MSFD). Changes in the dominance of these two phytoplankton classes impact the food web because both their quality as a food source for grazers and their periods of occurrence differ, which may lead to a mismatch in zooplankton growth. The rapid sinking of diatoms results in a high Dia/Dino index, indicative of low-level food availability for zooplankton but high-level food delivery to the zoobenthos. Consequently, the Dia/Dino index can be used to follow the food pathway (Descriptor 4 of MSFD: “food web”). Moreover, a low Dia/Dino index may indicate silicate limitation caused by eutrophication, whereas a high Dia/Dino index supports mitigated eutrophication, as the strong sedimentation of nutrients removes them from the water and deposits them in the sediment (Descriptor 5 of MSFD: “eutrophication”). Diatom dominance, and thus a high Dia/Dino index, is typical in historical data and is therefore assumed to reflect good environmental status (GES). The principles of the Dia/Dino index are explained herein using examples from two very different regimes, the Eastern Gotland Basin and Kiel Bay. In the assessment of the environmental status of these water bodies, GES boundaries of 0.5 and 0.75, respectively, are suggested. The conditions for calculating the Dia/Dino index are described and the limitations and advantages of this indicator are discussed.